Impact of Macroeconomic Variables on Stock Returns: A Case Study from Karachi Stock Exchange - HAMZA KHWAJA; NIDA JAMAL; SAQIB SHAHZAD (Journal of Business & Tourism, 2021)
The main theme behind this research is to find out how different macroeconomic variables affect the returns of the Karachi stock exchange. The three variables like interest rate, inflation rate and exchange rate which are taken under consideration are the back bone of any economy and this impact the economy in different ways if some sort of fluctuations occurs in these variables. Fifteen years annul data from 1992 to 2007 is taken and multiple regression models applied on this data. The results are very significant and the strong correlation is found among dependent and independent variables which shows that the model is a strong model. The impact of interest rate, exchange rate and inflation rate are significant on the stock returns of KSE 100 index